Some metric characterizations of commutativity in C*-algebras - Florin Pop (Surveys in Mathematics and its Applications)
We study Le Page's theorem in the context of C*-algebras and obtain several characterizations of commutativity and centrality implied by identities or inequalities satisfied by the norm.